Chemical Response of the Upper Atmosphere Due to Lightning‐Induced Electron Precipitation. Issue 17 (26th August 2021) - Xu, Wei; Marshall, Robert A.; Kero, Antti; Sousa, Austin
Abstract: Terrestrial lightning frequently serves as a loss mechanism for energetic electrons in the Van Allen radiation belts, leading to lightning‐induced electron precipitation (LEP). Regardless of the specific causes, energetic electron precipitation from the radiation belts in general has a significant influence on the ozone concentration in the stratosphere and mesosphere. The atmospheric chemical effects induced by LEP have been previously investigated using subionospheric VLF measurements at Faraday station, Antarctica (65.25°S, 64.27°W, L = 2.45). However, there exist large variations in the precipitation flux, ionization production, and occurrence rate of LEP events depending on the peak current of the parent lightning discharge, as well as the season, location, and intensity of the thunderstorm activity. These uncertainties motivate us to revisit the calculation of atmospheric chemical changes produced by LEP. In this study, we combine a well‐validated LEP model and first‐principles atmospheric chemical simulation, and investigate three intense storms in the year of 2013, 2015, and 2017 at the magnetic latitude of 50. 9 °, 32. 1 °, and 35. 7 °, respectively. Modeling results show that the LEP events in these storms can cumulatively drive significant changes in the N O x, H O x, and O x concentration in the mesosphere. These changes are as high as ∼ 156 %, ∼ 66 %, and − 5 % at 75–85 km altitude, respectively, and comparable to the effects typically induced by other types of radiation belt electron precipitation events. Considering the high occurrence rate of thunderstorms around the globe, the long‐term global chemical effects produced by LEP events need to be properly quantified. Key Points: We quantify the atmospheric chemical response due to lightning‐induced electron precipitation (LEP) using first‐principles simulations The change in ozone concentration during one thunderstorm via LEP processes is comparable to other types of energetic particle precipitation The long‐term global chemical effects produced by LEP events could be potentially important and need to be properly quantified